Healthcare Access and Regional Inequalities as Determinants of Childhood Stunting in East Nusa Tenggara, Indonesia: A Systematic Review - Arif Andriyanto; Ardian S. Leky (Epidemiology and Society Health Review (ESHR), 2026)
Background: Stunting remains a major public health problem in Indonesia, particularly in East Nusa Tenggara (NTT) Province, which has the highest prevalence of stunting nationally. The high incidence of stunting in NTT is influenced not only by inadequate nutrition but also by limited access to health services, clean water, and sanitation, as well as socioeconomic and development disparities between regions. Method: This study employed a systematic review method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A systematic literature search was conducted through Google Scholar, PubMed, and Garuda databases using the keywords "stunting," "access to health services," "regional inequality," and "East Nusa Tenggara." A total of 1,653 articles were found in the initial search phase, and 12 met the criteria for further analysis. Results: The study results show that stunting in East Nusa Tenggara is closely related to various multidimensional factors, including limited access to sanitation and clean water, minimal health care facilities, geographic isolation, poverty, and inequality between rural and urban areas. Conclusion: Stunting in East Nusa Tenggara is a multidimensional problem. Therefore, efforts to address stunting in NTT require an integrated, cross-sectoral approach that emphasizes equitable access to health services, improved sanitation, clean water provision, poverty alleviation, and region-based development.